Funções não-representativas no design gráfico pós-moderno - Cardoso, Tarcísio de Sá (2010)
This research seeks to understand the mechanisms of non-representational contemporary graphic design. The expression "non-representative" is intended to connote some kind of sign that is characterized by polysemy. In print, this aspect has insisted to emerge in many different manifestations. Despite its recurrence, this type of sign has not received the deserved attention by the scientific community, especially in regarding to the theory of signs an instrument that seems privileged to explain the functions of language presented there. Called unreadable and dysfunctional, the graphic design of David Carson, Neville Brody, Edward Fella, April Greiman and many others are still currently subject of contents. To be more specific, we may say that all post-ulmian vanguard from around the world, questions the rationality of an area so close to the arts, and represents a kind of counterpoint to the canonical approach, which from the Bauhaus and constructivism tries to articulate an exclusivist disciplinarity to the design. This objection became important especially in Europe (HOLLIS, 2001) and in the USA (MCCOY, 1990), in which new wave movement has its most characteristic representation. One of the theorists that works with the evolution of the modernist slogan form follows function, Bürdek presents the problem of function in a new outlook not anymore as an exclusively practical function, but mainly what he called a sign function. According to him, these are the most important functions for design (BÜRDEK, 2002). From this point of view, we intend to answer how these sign functions are articulated in visuality of post-modern design from the 1990s, to build communication processes that dialogue with the culture of information, or the culture in which the sign function overcome the function of use (BAUDRILLARD, 1995). Differently from the structuralist conception of the sign in Baudrillard it means by sign function, in this study, the processes that substantiate the sign according to Peirce's semiotics (on aspects of quality, existence and regularity). From this perspective, we will intend a deeping in trichotomies of visual language as presented in matrix theory of language-thought (SANTAELLA, 2005). These trichotomies will be essential to study the controversial expressions of contemporary graphic design, in order to identify what it is innovative, which is commonplace, which transcends the current publishing paradigm and what is considered, even today, polemic by the scientific community